POVERTY AND FOOD SECURITY OF THE FARMER HOUSEHOLDS IN KEDUANG SUBWATERSHED WONOGIRI DISTRICT - Ajeng Ayu Nabila Mandala; Suhatmini Hardyastuti; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This study aims to know human assets, natural, physical financial, and social to identify level of poverty and food security in critical and non critical land areas, to analyze factors affecting level of food security, to identify lingkages between poverty and food security. The research was conducted in Keduang Subwatershed Wonogiri District determined purposively covering upstream, widstream, and downstream which describes the land area of critical and non critical. The respondents are 120 farmers, randomly selected woth 20 farmers in each location. The result show that human assets ( age, education, farming experience, numbe r of household), natural ( land area, area assets). Physical (vehicles), financial (savings, jewelry, cuttle), social (solidarity, trust, and cooperation, conflict resolution) in the critical land areas are similar to the non critical, while agricultural equipment in critical land areas lower than then non critical. Poverty in the critical higher than the non critical areas based on criteria Sajogyo, World Bank, Asian Development Bank(ADB), and the Food and Agriculture Organization (FAO), whereas according to the criteria of BPS Wonogiri District in areas of critical and non critical landa not classified as poor. Food security in critical is lower than the non critical areas. Factors affecting food security are education, land area, number of households, food expenditure, non food expenditure. . Poverty and food security are intertwined, percentage of vulnerablewithin non poor households ara found enough high where sometime the vulnerable household be able to change into insecure category if the food supply is not sufficient.